Importance of legal education for quantity surveying professionals: a proposal for developing a legal studies module for Malaysian system - Maidin, Ainul Jaria; Sulaiman, Siti Sarah (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Teaching law to non law students raises concerns such as the relevance and extent of the content, ways of engaging the students, purpose of the modules and the learning outcome as well as the teaching pedagogy which facilitates the teaching and learning and delivery of knowledge. This article seeks to identify these issues to justify the need to incorporate legal education for professionals involved in land development and built environment professions in Malaysia coupled with the appropriate teaching pedagogy. The proposal aims as developing a legal studies module for the Malaysian system. Various methods engaged by the authors are explored, with particular concentration on the introduction of case studies / scenarios at an early stage of studies to ensure the relevance and practicality of the course, in the context of future careers, is better understood by all students. Quantity Surveyors profession provides the parties involved in construction advice and services associated with procurement, value and cost of projects from inception to completion, contract administration, project management, costing and other aspects concerning land development and building construction. The various areas of work involving the Quantity Surveyors require quite a substantial knowledge of various disciplines of law to meet the clients’ expectation of the service offered by quantity surveyors and this coupled with greater competition both internally (from the profession) and externally that has resulted in a challenge to their professional status. To meet these challenges quantity surveyors need to enhance their professionalism and status in order that practitioners can maintain a competitive advantage. Legal knowledge is an important key feature of the surveyor's portfolio and therefore can help to improve their expertise. As the quantity surveying profession is subject to challenges and competition the proposed paper will explore the rationale for incorporating legal education for Quantity Surveyors profession and the suggested legal studies modules to equip these professionals with the relevant legal related knowledge and skills.